Modelling co-movement and portfolio optimization of gold and global major currencies - Methas Rattanasorn (2018)
© Springer International Publishing AG 2016. This study aims to investigate the co-movement of gold and global major currencies. We propose several time-varying copula-based GARCH models to measure the co-movement of gold and exchange rate returns and construct the optimized portfolio under copula-based models with modern portfolio theory. The empirical results show that all of the exchange rates are positively correlated with gold, except for USD. With the exception of AUD and GBP, all other exchange rates exhibit a significantly time-varying dependence which is beneficial for portfolio diversification opportunities. We construct optimization problems based on modern portfolio theory and mean-variance portfolio. Our results suggest that the maximum Sharpe ratio portfolio outperformed both an equally weighted portfolio and a conventional Markowitz portfolio model. Finally, USD and gold are the best portfolio and their cumulative return of investment is about 20% over five years.